Design, Estimate, Costing and Execution of a Two Tier Outdoor Fountain - Lohani, T. K; Dash, K.P; Jena, S.K; Parida, P.K (Journal of Asian Scientific Research, 2016)
A two tier outdoor fountain was designed to showcase the ornamental work and functionality of a concrete structure. The fountain is 3800 mm. The size of the footing mat is 1800mm X 1800mm. Diameter of the column is 450mm. The overall thickness of foundation is 350mm whereas the thickness at the edge is 200mm. The concrete used for the entire construction is of either M15 or M20 grade. This thickness was designed based on the requirement of bending, punching shear and beam shear. Two bowls were constructed at a certain height distance apart. The top of the fountain gives a shape of an earthen water pot with an opening at the top. The opening is fitted with a foam shower. There are 64 Nos. of nozzle jets are fitted all along in the inner part of the parapet wall in circumferential pattern that throws water to the bowls. Finally a 1HP pump is installed inside the static water storage of the fountain and four Nos. of coloured water proof flood lights were fitted at four elevated corners. The total cost of the fountain is estimated around one lakh forty six thousand and seventy two only in INR till execution. The design parameters are prepared by the authors taking different design factors.